Comparative analysis reveals Ce3D as optimal clearing method for in toto imaging of the mouse intestine. Issue 5 (13th February 2019) - Bossolani, Gleison D. P.; Pintelon, Isabel; Detrez, Jan D.; Buckinx, Roeland; Thys, Sofie; Zanoni, Jacqueline Nelisis; De Vos, Winnok H.; Timmermans, Jean‐Pierre
Abstract: Background: The intestinal wall has a complex topographical architecture. The multi‐layered network of the enteric nervous system and its intercellular interactions are difficult to map using traditional section‐based or whole‐mount histology. With the advent of optical clearing techniques, it has become feasible to visualize intact tissue and organs in 3D. However, as yet, a gap still needs to be filled in that no in‐depth analysis has been performed yet on the potential of different clearing techniques for the small intestine. Aim: The goal of this study was to identify an optimal clearing protocol for in toto imaging of mouse intestinal tissue. Methods: Five aqueous‐based clearing protocols (SeeDB2, CUBIC, ScaleS, Ce3D, and UbasM) and four organic reagent‐based clearing protocols (3DISCO, iDISCO+, uDISCO, and Visikol ® ) were assessed in segments of small intestine from CX3CR1 GFP/GFP and wild‐type mice. Following clearing, optical transparency, tissue morphology, green fluorescent protein (GFP) fluorescence retention, and compatibility with (immuno‐)labeling were analyzed. Key results: All organic reagent‐based clearing protocols—except for Visikol—rendered tissue highly transparent but led to substantial tissue shrinkage and deformation. Of the aqueous‐based protocols, only Ce3D yielded full‐thickness tissue transparency. In addition, Ce3D displayed excellent GFP retention and preservation of tissue morphology. Conclusions: Ce3D emerged as a most efficient protocol for enabling rapid full‐thickness 3D mapping of the mouse intestinal wall. Abstract : Comparison of five aqueous‐based (SeeDB2, CUBIC, ScaleS, Ce3D and UbasM) and four organic reagent‐based clearing protocols (3DISCO, iDISCO+, uDISCO and Visikol) yielded Ce3D as a most efficient protocol for enabling rapid full‐thickness 3D mapping of the mouse intestinal wall.